2018
DOI: 10.1109/jsen.2017.2780163
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Terbium-Activated Gadolinium Oxysulfide Plastic Optical Fiber Sensor in Photons and Protons

Abstract: Abstract-A characterization study was carried out to determine if a novel, millimetre sized Terbium-activated Gadolinium Oxysulfide optical fibre detector has potential for future use in proton dosimetry. Preliminary studies employed a Theratronics Theratron 780C Cobalt-60 unit and were used to determine nominal dose response, field size response and Čerenkov contributions in 1.25 MeV gamma radiation. Extensive testing was done using 74 MeV protons produced in the TRIUMF 500 MeV cyclotron facility examining ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…However, the percentage differences between the OFS and the microdiamond and the W1 decreased with a decrease in field size from 17.4 ± 0.04%, 8.3 ± 0.04% and 5.4 ± 0.06% for 10x10 cm 2 , 4x4 cm 2 and 2x2 cm 2 , respectively. As the Gd2O2S:Tb scintillator is not a water equivalent material (Zeff = 64), the scattered radiation produced when the field sizes and/or the depth in phantom increases plays an important role in the overresponse of the OFS [15,19,20] When compared to other studies that employed scintillating material with high Z numbers, however, our results showed higher discrepancies across the investigated field sizes [15,20].This can be partly attributed to the Cerenkov radiation produced in the fibre itself and in the solid water phantom [21]. A 5% difference was reported by Martinez et al (2015) for their YVO4:Eu 3+ sensor when measuring PDD for a 3x3 cm 2 radiation field size with and without temporal filtration of Cerenkov at 10 cm depth [19].…”
Section: Percentage Depth Dose and Lateral Dose Measurementscontrasting
confidence: 61%
“…However, the percentage differences between the OFS and the microdiamond and the W1 decreased with a decrease in field size from 17.4 ± 0.04%, 8.3 ± 0.04% and 5.4 ± 0.06% for 10x10 cm 2 , 4x4 cm 2 and 2x2 cm 2 , respectively. As the Gd2O2S:Tb scintillator is not a water equivalent material (Zeff = 64), the scattered radiation produced when the field sizes and/or the depth in phantom increases plays an important role in the overresponse of the OFS [15,19,20] When compared to other studies that employed scintillating material with high Z numbers, however, our results showed higher discrepancies across the investigated field sizes [15,20].This can be partly attributed to the Cerenkov radiation produced in the fibre itself and in the solid water phantom [21]. A 5% difference was reported by Martinez et al (2015) for their YVO4:Eu 3+ sensor when measuring PDD for a 3x3 cm 2 radiation field size with and without temporal filtration of Cerenkov at 10 cm depth [19].…”
Section: Percentage Depth Dose and Lateral Dose Measurementscontrasting
confidence: 61%
“…Since the linear energy transfer (LET) does change dramatically along the Bragg peak of proton therapy, the independence of both energy and dose rate are crucial characteristics in any new detector. Most scintillation detectors are known to exhibit increased quenching when LET increases 4,6,1217 due to the participation of alternate modes of energy dissipation in regions of high ionization density. In order to resolve the Bragg peak of the proton dose depth profile, a fiber diameter of 250 m or less may be required 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Except for photon-based RT and BT dosimetry, IOSFDs also demonstrate the potential for dosimetry in other types of therapy treatments such as PT and BNCT [73][74][75][76][77][78][79]. PT offers improved dose distribution compared to ionizing photon radiation.…”
Section: Iosfd For Other Types Of Particle Radiation Dosimetrymentioning
confidence: 99%
“…The IOSFDs reported in this area include a Gd 2 O 2 S:Tb-based detector and a lanthanide-doped silica scintillator-based detector [73][74][75]. Penner et al [73] investigated Gd 2 O 2 S:Tb-based IOSFD for photon and proton dosimetry. For proton dose detection, the detector exhibited excellent sensitivity, signal-to-noise ratio, and reproducibility.…”
Section: Iosfd For Other Types Of Particle Radiation Dosimetrymentioning
confidence: 99%
See 1 more Smart Citation